2020
DOI: 10.1029/2019jb018794
|View full text |Cite
|
Sign up to set email alerts
|

Stress Transfer From Opening Hydraulic Fractures Controls the Distribution of Induced Seismicity

Abstract: Understanding the dominant physical processes that cause fault reactivation due to fluid injection is vital to develop strategies to avoid and mitigate injection-induced seismicity. Injection-induced seismicity is a risk for several industries, including hydraulic fracturing, geothermal stimulation, oilfield waste disposal and carbon capture and storage, with hydraulic fracturing having been associated with some of the highest magnitude induced earthquakes (M > 5). As such, strict regulatory schemes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 72 publications
(113 reference statements)
4
49
0
Order By: Relevance
“…In this sense, the temporal evolution of earthquake swarms does not tend to follow traditional fore/main/aftershock patterns (Hill, 1977; Mogi, 1967). This swarm‐like character is in accord with closer assessments of HF‐induced earthquakes, where interevent times follow a nonhomogeneous Poisson distribution (Hajati et al, 2015) with smaller contributions from earthquake interactions (Catalli et al, 2016; Kettlety et al, 2019; Maghsoudi et al, 2018). This is not surprising, as stage‐by‐stage stimulation can sequentially illuminate faults.…”
Section: Common Themessupporting
confidence: 72%
See 2 more Smart Citations
“…In this sense, the temporal evolution of earthquake swarms does not tend to follow traditional fore/main/aftershock patterns (Hill, 1977; Mogi, 1967). This swarm‐like character is in accord with closer assessments of HF‐induced earthquakes, where interevent times follow a nonhomogeneous Poisson distribution (Hajati et al, 2015) with smaller contributions from earthquake interactions (Catalli et al, 2016; Kettlety et al, 2019; Maghsoudi et al, 2018). This is not surprising, as stage‐by‐stage stimulation can sequentially illuminate faults.…”
Section: Common Themessupporting
confidence: 72%
“…Admittedly, these observations are often obscured because of the narrowing gap in between stage simulations from increasingly fast completion pacing and styles (e.g., zipper fracks). However, there are noteworthy cases during the initial development of HF where simpler and slower completions caused earthquakes (Friberg et al, 2014; Kettlety et al, 2019). For example, in December of 2011 near Cardston, Alberta (Schultz, Mei, et al, 2015) a single‐well pad was completed with ~24 hr between stages.…”
Section: Common Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the large wastewater disposal‐induced events in Oklahoma triggered typical aftershock behavior (Keranen et al, 2014; McGarr & Barbour, 2017), while the HF‐induced clustering near Youngstown, Ohio, and injection‐related events in central Arkansas, near Guy and Greenbrier, displayed swarm‐like characteristics (Horton, 2012; Llenos & Michael, 2013; Skoumal et al, 2015). Studies have shown that both natural and anthropogenic changes to the subsurface fluid content can enhance or induce clustered earthquake sequences via subsidence and changes in Coulomb fault stress or pore pressure conditions, especially near critically oriented structures (Bao & Eaton, 2016; Brodsky & Lajoie, 2013; Goebel et al, 2015; Keranen et al, 2014; Kettlety et al, 2019, 2020; Kumazawa & Ogata, 2013; Langenbruch & Shapiro, 2010; Schoenball et al, 2015; Segall, 1985). The nature of clustering observed within a region may be attributed to its rheological structure, in the framework of viscoelastic deformation (Ben‐Zion & Lyakhovsky, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Awareness and concern regarding the impacts of seismicity induced by hydraulic fracturing have grown significantly in recent years (e.g Ellsworth, 2013;Davies et al, 2013;Cotton et al, 2014;Whitmarsh et al, 2015;Williams et al, 2017;Atkinson et al, 2020), which may pose a threat to the future development of unconventional gas resources (Kraft et al, 2009). There is evidence that tolerance of such operations will be increased if the public is made aware of the potential consequences of the resulting ground shaking (Giardini, 2009;Bommer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%